Desire to end violence: Human rights and intercultural citizenship in teacher education - Amez, Mariel (Argentinian Journal of Applied Linguistics - ISSN 2314-3576, 2022)
An intercultural citizenship perspective should be included in all levels of education, and pre-service teacher programmes are no exception. Teachers themselves should be committed citizens of a world community in order to teach their students to uphold rights and obligations based on common human values. This project describes an interdisciplinary approach to the theme of women’s rights in initial teacher education: it starts with work on A streetcar named desire as a springboard for the discussion of domestic violence and broadens the topic through the integration with the contents of core subjects. The sections for each content area, which are relevant to specific course aims as well as to human rights education, can also be used on a stand-alone basis.